Palladium Supported on Calcium Decorated Carbon Nanotube Hybrids for Chemoselective Hydrogenation of Cinnamaldehyde - Ma, Ying; Feng, Lu; Guo, Zhanglong; Deng, Jiangtao; Pham-Huu, Cuong; Liu, Yuefeng (Frontiers in Chemistry, 2019)
The chemoselective hydrogenation of cinnamaldehyde (CAL) to the corresponding hydrocinamaldehyde (HCAL) is a type of important reactions in fine chemistry, which is critically dependent on the rational design the chemical structure of active metal. In this work, calcium promoted palladium on CNT hybrid (Ca-Pd@CNT) with monolithic structure was synthesized through one-pot alginate gel process. The catalytic performance results showed that moderate Ca promotion catalyst (Ca-Pd@CNTHCl-2h) present a superior CAL hydrogenation activity with CAL conversion of 99.9% and HCAL selectivity of 86.4% even at the lager Pd nanoparticle size (c.a. 5 nm). The characterization results show that the electron transfer between the additive Ca promoter and Pd nanoparticles (NPs) could modify the electron structure of Pd species and induce the formation of the partial positively charged Pdδ+ species on the Pd NPs surface in the Ca-Pd@CNTHCl-2h catalyst resulting the satisfactory catalytic performance. Furthermore, the one-pot gel synthesis methodology for microscopic carbon supported catalyst could also endows its great potential industry application in heterogeneous catalysis with easily handling during the transportation and reaction, and attributed to reducing the overall pressure drop across in the fix-bed reactor.